PENGEMBANGAN PERMAINAN MONOPOLI SEBAGAI MEDIA PEMBELAJARAN SEJARAH PADA SISWA KELAS X SMA NEGERI 3 MUARO JAMBI - Khairani, Dini Elvita; Pamungkas, Satriyo (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2022)
This research and development was taken from the problems that occurred in SMA Negeri 3 Muaro Jambi where the learning was monotonous and less varied so that students felt bored quickly and their attention was quickly distracted by other things. Learning media can be an alternative in solving problems that occur in schools. This study aims to produce a learning media product, namely Monopoly Game which applies the elements of playing and learning into one in class X history lessons at SMA Negeri 3 Muaro Jambi. The research model used in this study is ADDIE developed by Lee and Owen which consists of Analysis, Design, Development, Implementation, and Evaluation. This research was conducted at SMA Negeri 3 Muaro Jambi with the research subjects of Class X students, totaling 4 people for individual trials, 14 people for small group trials, and 30 for large group trials. From the results of the field trials, the results of individual trials were obtained with an average score of 72% in the "good" category, Small Group trial results with an average score of 75% in the good category, Field Group trial results with an average score the percentage of 81 with the "very good" category for learning this monopoly game can be applied in history learning.